2016
DOI: 10.1186/s40550-016-0034-6
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial usage in the chicken farming in Yaoundé, Cameroon: a cross-sectional study

Abstract: Background: Antimicrobials are widely used in chicken production in Cameroon, but no quantitative data are available. A cross-sectional survey was conducted in 98 farms holding 220,262 chickens, from February to May 2015 in six areas of Yaoundé, the capital of Cameroon, to describe and quantify the use of antimicrobials. Results: All the farms were using antimicrobials via drinking water administration. Twenty types of drugs containing antimicrobials belonging to 9 classes were recorded. 19.4 % of farms used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 25 publications
4
10
1
Order By: Relevance
“…Quinolones, classified as WATCH drugs, were the most frequent antibiotics (38% of all) given at farms. These results were consistent with previous reports in the country, where around 30% and 57% of antibiotics used were quinolones [ 11 ]. Persistent use of quinolones for prophylactic purposes conducted over a three-year period of time shows low implementation of international recommendations and also demonstrates shortcomings in regulatory activities.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Quinolones, classified as WATCH drugs, were the most frequent antibiotics (38% of all) given at farms. These results were consistent with previous reports in the country, where around 30% and 57% of antibiotics used were quinolones [ 11 ]. Persistent use of quinolones for prophylactic purposes conducted over a three-year period of time shows low implementation of international recommendations and also demonstrates shortcomings in regulatory activities.…”
Section: Discussionsupporting
confidence: 93%
“…We observed a very high proportion (>90%) of prophylactic antibiotic use compared to previous reports from Cameroon: 4% and 11% in 2015, respectively [ 11 , 12 ]. Different methods to assess use of antibiotics could be one explanation for the difference observed.…”
Section: Discussioncontrasting
confidence: 57%
“…So, quinolones are very helpful for human beings against many bacterial infections and they should be used with great precautions in breeding [27]. As known, nitro furans have been banned from use in food-producing animals since 1991 in the United States and 1995 in the European Union because of concerns over the carcinogenicity of these compounds [28][29][30]. In the present study, the use of banned substances such as nitro furans, which represented 11.1 % of total used in quantitative terms, was recorded and this also is a great concern.…”
Section: Results and Discussion Antibiotic Usage Practicesmentioning
confidence: 99%
“…Only 25.4% (230) of households surveyed were aware of the use of chemicals in chicken farming by farmers. Gondam et al, and Guiteya et al, reported that veterinary drugs are improper used by farmer in chicken farming in Cameroon [15,17]. These latter reported that the use of antibiotics as growth promoters in developing countries such as Cameroon, allows Cameroonian to purchase at reasonable cost, high quality meat and eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, factors influencing consumption of chicken and eggs are not well known. Such situations are too embarrassing due to poultry sector performing, public nutrition and health problems, the more as veterinary drugs have been reported as being used by farmers above the recommended concentrations in this country [15,17]. This study was therefore designed to assess the health risk that can be associated through the collection of production and consumption data.…”
Section: Introductionmentioning
confidence: 99%